The Development of Family 10 Learning Model to Improve Social Studies Outcomes for 5th Grade - Divina P, Amina; Rosyada Mahmud, Dini; Setyosari, Punaji; Alfan, Muhammad (KnE Social Sciences, 2023)
The family 10 learning model is a learning model designed based on active and fun team quiz-based cooperative learning. This study aims to describe the effectiveness of the Family 10 model to improving student learning outcomes in class V social studies content. This research is a research and development type carried out in Sampang District. The results of the study support that the Family 10 learning model can improve student learning outcomes based on the results of data analysis which shows a significant difference between the KKM (minimum completeness criteria) score and the value after the Family 10 model is applied. Keywords: Learning model Class V Innovation Social Studies